Rehabilitation of pelvic fracture - Yosuke Nagai (Japanese Society of Physical Fitness and Sports Medicine, 2024)
Rehabilitation protocols for treating pelvic fractures lack uniformity due to variations among patients, injury mechanisms, and fracture types. The incidence of pelvic fragility fractures in the elderly has risen in recent years, prompting discussions on treatment strategies, including conservative approaches. This article aims to conduct a literature review of rehabilitation practices following pelvic fractures reported up to September 2023, to elucidate the current state of the field. We conducted a search on PubMed for literature published prior to September 2023. No systematic selection was applied to articles published thereafter. The search criteria excluded non-English publications, case reports, pediatric fractures, and studies where the primary outcome did not focus on clinical aspects of pelvic fractures. We included a total of 201 papers, narrowing it down to 35 through title and abstract screening. This article described loading protocols, sexual dysfunction, mental dysfunction, surgical techniques and methods of functional assessment. Rehabilitation policies vary, often determined on a case-by-case basis, specifically by individual surgeons or treatment centers. No unified protocols exist at present, but future research will hopefully lead to significant progress.